Pembinaan Keagamaan Dan Literasi Untuk Meningkatkan Hubungan Sosial Di Masyarakat Ulujami Jakarta Selatan - Much. Hasan Darojat; Irfandi Rizky Tomagola; Ahmad widadi faatihul uula (Jurnal Pengabdian Masyarakat (Bisma), 2024)
The community service program implemented in the form of Community Service Learning (KKN) aims to assist the community in enhancing their understanding of religious knowledge and literacy skills. Additionally, this community service seeks to strengthen the bonds of brotherhood among community members and between the academic world and the community. This service is carried out through social activities within the local community. The students also collaborate with the Al-Qur'an Education Park Foundation (TPQ) al-Bait al-Jamil to provide tutoring sessions for the community. The approach to these activities includes teaching religious materials, conducting language classes, and introducing literacy in both digital and non-digital forms. Furthermore, this program provides parenting workshops for parents on how to educate their children and develop their creativity in ways that align with Islamic teachings. The results of the implementation of this community service activity show that community members, including parents and school children from elementary and secondary levels, participate enthusiastically in the learning of religious knowledge and literacy. Finally, the evaluation of this project revealed that there are some social conflicts amongts the residents in the area due to a gap in their occupational backgrounds. This may bring the disparity in this community. Hence, by this community service hopefully would help them to strengthen their relationship